2008
DOI: 10.1007/s12275-008-0087-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of immunotherapeutic effects of HPV16E7 on cervical cancer by fusion with CTLA4 extracellular region

Abstract: Cervical cancer is caused by infection by high-risk human papillomavirus (HPV), especially HPV16. Limitations in current treatments of cervical cancers call for the development of new and improved immunotherapies. This study aims at investigating the efficacy of a novel vaccine consisting of modified HPV 16E7 fused with human cytotoxic T-lymphocyte antigen 4 (CTLA4). The regions in HPV16 E7 gene associated with its transformation and CTL-enhanced response were modified; the resultant HPV16mE7 was fused with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…2). These properties have not been reported previously for any DC-targeted vaccine containing HPVE7 antigens 23,26 and represent a major improvement over other targeting moieties. Indeed, it has been shown that when DCs fail to mature after taking up the antigen the outcome may be tolerance rather than immunity.…”
Section: Discussionmentioning
confidence: 58%
“…2). These properties have not been reported previously for any DC-targeted vaccine containing HPVE7 antigens 23,26 and represent a major improvement over other targeting moieties. Indeed, it has been shown that when DCs fail to mature after taking up the antigen the outcome may be tolerance rather than immunity.…”
Section: Discussionmentioning
confidence: 58%
“…2). These properties have not been reported previously for any DC‐targeted vaccine containing HPVE7 antigens23, 26 and represent a major improvement over other targeting moieties. Indeed, it has been shown that when DCs fail to mature after taking up the antigen the outcome may be tolerance rather than immunity 6, 8, 10, 27.…”
Section: Discussionmentioning
confidence: 59%
“…The culture supernatants were lyophilized and resuspended in 300 µL of PBS. The levels of IFN-γ in culture supernatant of mice lymphocytes that were immunized with HCV1b-E2 protein and HCV1b-E2-PLGA microspheres were compared using the IFN-γ ELISA kit 25 (Dakewe Biotech Co. Ltd., Beijing, People's Republic of China) according to the manufacturer's instructions. Mice IFN-γ standard proteins at 40, 20, 10, and 5 pg were measured as the standard point of OD at 450 nm.…”
Section: Ifn-γ Elisa Assaymentioning
confidence: 99%